DESEMPENHO PRODUTIVO DE MARACUJAZEIRO AMARELO EM ÁREA COM Fusarium solani (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The use of grafting in tolerant rootstocks has shown good results in contolling Fusarium wilt in yellow passion fruit, considered one of the main problems in the crop, which affects the plant’s root system and has no chemical control. The presennt study aimed to evaluate the survival, the agronomic performance of plants and the physical characteristics of yellow passion fruit (Passiflora edulis Sims) grafted on three rootstocks in area with Fusarium wilt. The experiment was carried in Pracinha, São Paulo State, Brazil, from August 2014 to May 2015, and a randomized block design was adopted, with five treatments and five replications. The treatments were constituted by rootstocks: Passiflora alata Dryand, Passiflora gibertii N.E. Brown, Passiflora caerulea Linnaeus, double grafting P. gibertii x P. edulis and plants without grafting. The stem diameter of rootstock and the graft, the lenght of secondary branches, the number of tertiary branches, the number of surviving plants, the longitudinal and transversal diameters of the fruits, the number and mass of fruits and the productivity were evaluated. The highest survival rates were observed in P. alata with 90% and P. gibertii with 100% survival. The highest number of fruits per plant and productivity occurred in plants grafted on P. gibertii. The adoption of double grafting using P. gibertii x P. edulis and simple grafting with P. caerulea were not effective in contgrolling this disease. The rootstocks P. alata proved to be the most vigorous material as a rootstock.